2021
DOI: 10.1371/journal.pone.0246566
|View full text |Cite
|
Sign up to set email alerts
|

Land use/land cover change, physico-chemical parameters and freshwater snails in Yewa North, Southwestern Nigeria

Abstract: The management of ecosystem has been a major contributor to the control of diseases that are transmitted by snail intermediate hosts. The ability of freshwater snails to self-fertilize, giving rise to thousands of hatchlings, enables them to contribute immensely to the difficulty in reducing the endemicity of some infections in the world. One of the effects of land use/land cover change (LU/LCC) is deforestation, which, in turn, leads to the creation of suitable habitats for the survival of freshwater snails. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Snail abundance varied significantly across the five parts of the study area characterized by different land uses, with the highest abundance observed in villages and the lowest in the farm section. Consistent with previous studies (Du et al, 2011; Lange et al, 2013; Oso & Odaibo, 2021), our findings underscore the profound impact of anthropogenic environmental changes on freshwater mollusc communities. Research suggests that snails tend to thrive in environments altered by human activities.…”
Section: Discussionsupporting
confidence: 92%
“…Snail abundance varied significantly across the five parts of the study area characterized by different land uses, with the highest abundance observed in villages and the lowest in the farm section. Consistent with previous studies (Du et al, 2011; Lange et al, 2013; Oso & Odaibo, 2021), our findings underscore the profound impact of anthropogenic environmental changes on freshwater mollusc communities. Research suggests that snails tend to thrive in environments altered by human activities.…”
Section: Discussionsupporting
confidence: 92%
“…Low dissolved oxygen levels indicate poor water quality from organic and anthropogenic pollution. Furthermore, low oxygen content in water affects the development of intermediate host snails hence reduction in snail abundance, egg size, and variations in shapes [ 37 ]. This low oxygen in water also increases the active organic decomposition of the sediments, leading to the suffocation and death of freshwater snails.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of vegetation for crop farming results in habitat fragmentation and increasing sunlight penetration. This creates favorable conditions for the survival of snail species and is expected to increase the risk of trematode infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of a forest ecosystem into agricultural land profoundly affects stream morphology, water chemistry, increased levels of siltation, altered nutrient dynamics, and hydrology [ 16 ]. This creates favorable conditions for the survival of snail species and is expected to increase the risk of trematode infection [ 17 ]. The widespread deforestation and degradation of natural habitats for crop farming and grazing of animals could also contribute to the loss of aquatic biodiversity including snail predators and competitors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%